The dental and oral status of children with chronic renal failure - Nakhjavani Yahya; Bayramy Ali (Wolters Kluwer Medknow Publications, 2007)
The main purpose of this investigation was to evaluate the oral and dental status of chronic renal failure (CRF) patients undergoing hemodialysis at children′s Hospitals in Tehran. Fifty-three children with CRF aged 5-18 years recruited from the renal unit of children′s medical center, Tehran Hospitals for children, were studied. The decayed, missing, filled dmf, DMF, and MGI scores were recorded. The CRF children had low prevalence of dental caries, although none of the clinical diagnoses displayed the absence of gingival inflammation. Duration of dialysis and Anemia had a significant influence on the gingival condition. Especially anemia leads to severe gingivitis. The CRF children need careful monitoring and all such patient should be given oral hygiene education as topmost priority.